2012
DOI: 10.1021/ac300611n
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Complete Isotopomer Distribution of Aspartate Using Gas Chromatography/Tandem Mass Spectrometry

Abstract: We have developed a simple and accurate method for determining the complete positional isotopomer distribution of aspartate carbon atoms by gas chromatography/tandem mass spectrometry for (13)C-metabolic flux analysis. First, we screened tandem mass spectrometry (MS) spectra of the tert-butyldimethylsilyl (TBDMS) derivative of aspartate for daughter fragments with the necessary carbon atom fragmentations to fully resolve all 16 isotopomers of aspartate. Tandem MS scanning parameters were optimized for each dau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 26 publications
0
63
0
Order By: Relevance
“…In particular, we identified that C. acetobutylicum produces isoleucine exclusively via citramalate synthase, which is likely encoded by the CAC3174 gene. In future work, we plan to focus on further elucidating the regulation of the pyruvate-tofumarate pathway using new analytical techniques, recently developed in our lab based on tandem mass spectrometry (Antoniewicz, 2013c;Choi and Antoniewicz, 2011), which can allow complete resolution of aspartate labeling (Choi et al, 2012), and using new dynamic metabolic flux analysis approaches (Antoniewicz, 2013b;Leighty and Antoniewicz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we identified that C. acetobutylicum produces isoleucine exclusively via citramalate synthase, which is likely encoded by the CAC3174 gene. In future work, we plan to focus on further elucidating the regulation of the pyruvate-tofumarate pathway using new analytical techniques, recently developed in our lab based on tandem mass spectrometry (Antoniewicz, 2013c;Choi and Antoniewicz, 2011), which can allow complete resolution of aspartate labeling (Choi et al, 2012), and using new dynamic metabolic flux analysis approaches (Antoniewicz, 2013b;Leighty and Antoniewicz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…By cleaving molecules into successively smaller fragments and measuring the resulting mass isotopomer distributions of daughter fragments detailed positional labeling information can be obtained. This was utilized to its fullest extent by Choi et al [34 ], who measured, for the first time, the complete isotopomer distribution of aspartate. Choi identified five parentdaughter fragment pairs that provided a redundant set of 47 isotopic measurements from which all 16 isotopomers could be deduced.…”
Section: Isotopomer Measurements By Gc-ms/msmentioning
confidence: 99%
“…Mass isotopomers of the resulting C2-C3 daughter fragment were measured by MRM. Choi showed that tandem mass isotopomer distributions measured for the selected fragments provided sufficient information to calculate all isotopomers by simple linear regression [34 ]. Similar strategies are under development for measuring complete labeling distributions of other molecules of interest for 13 C-flux analysis [35,36].…”
Section: Isotopomer Measurements By Gc-ms/msmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, 13 C MFA has been increasingly used in the past decade for quantifying pathway fluxes in microbial and mammalian systems Antoniewicz et al, 2006b;Sauer, 2006;Suthers et al, 2007). In 13 C MFA, fluxes are estimated by fitting isotopic labeling measurements, e.g., mass spectrometry (MS) (Wittmann and Heinzle, 1999), tandem MS Choi et al, 2012), and NMR (Szyperski, 1998) data, and extracellular uptake and excretion rates to an assumed metabolic network model. 13 C MFA consists of three main steps.…”
Section: Introductionmentioning
confidence: 99%